Professor G. F. Parrot in the struggle for the development of primary education in Ostsee provinces - Yulia Gracheva (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия ИИ. История, история Русской Православной Церкви)
The article analyses activities of Georg Friedrich Parrot, professor at the University of Dorpat, related to the emergence and development of primary schools in Ostsee provinces of the Russian Empire. The local nobility, who maintained parish schools at their own expense, wanted to control them even after the approval of the school charter on November 5, 1804. In order to place primary education under the control of the University of Dorpat, as well as to increase the number of primary schools in the territories of Livonian, Estland, Courland and Finland provinces, Professor Parrot proposed for approval to Emperor Alexander I his project on the establishment of parish schools in the district, which diff ered from those already adopted ministerial decrees. Despite the approval of the project by the Emperor, with whom Parroth had close friendship, the Dorpat professor’s plan received signifi cant objections from the members of the Main schools’ directorate. The author comes to the conclusion that the difficult financial situation caused by the military confl ict with France did not allow the Tsar to approve a special system of primary schools in the Baltic States, which required signifi cant fi nancial help from the treasury. The still unpublished correspondence between the Emperor and the Dorpat professor is introduced into scientifi c circulation, which makes it possible to signifi cantly supplement the current notion of the reforms of public education in the fi rst decade of the 19th century.